DETERMINATION OF POWER PROFILE OF HYDRO RESOURCESIN UNGAUGED CHANNELS - Luqman Muhammed Audu (Journal of Research in Engineering and Applied Sciences, 2020)
The diversification of the Nigeria power generation base requires the exploitation of Nigeria potential hydroelectric power resources which involves the evaluation of the flow characteristics of rivers to determine the hydro power profile and output. This process continues to constitute a daunting challenge in developing countries with poor meteorological and hydrological data base with non-functional gauging channels. The study presents a reliable model for fast, simple and accurate determination of flow characteristics in the hydroelectric power capacity evaluation for rivers and channels in poorly gauged areas and countries like Nigeria. Annual measurements were carried out on River Orle with factors like channel geometry, average monthly velocity and flow rate, and associated potential hydro power determined. The developed modelwas automated with a Mathcad 14.0 template andvalidated by comparing its results with the analytical measurement evaluation process of hydropower for different channels. The model output indicates that it has 100% accuracy and precision compared with the analytical processwhile being faster and userfriendly.The results indicate that River Orle has peak power production potentials of 18 MW, base power of 12 MW and low power output of 5MW. The river is capable of yielding power throughout the year